Reasons of internally displaced Kurdish women for not participating in educational programs in PECs: a narrative analysis - Zengin, Aslıhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This thesis aims to explore the reasons of internally displaced Kurdish women living in Bayramtepe, İstanbul for not participating to vocational and literacy courses provided by PECs (People’s Education Centers) through an analysis of their own perceptions of their life stories. The study employs narrative inquiry, categorical-content analysis in particular, to gain insight into the reasons of internally displaced Kurdish women for not participating in vocational and literacy courses served by PECs. Semi-structured interviews were carried out with 9 Kurdish women between ages 26-51 in Bayramtepe, Küçükçekmece. Narrative analysis of the data led to the formation of several outstanding themes. Discrimination based on ethnicity and language, demand for education in mother tongue, suppression of the husband and the immediate family, burden of children and the household duties, and health problems emerged as the most common factors that hindered women from participating or continuing further to educational activities. Internally displaced Kurdish women’s nonparticipation to adult educational activities has been discussed within the concepts of mother tongue, patriarchal family structure, ethnic background, internal displacement, and in accordance with literature on effects of displacement on women. Along with some factors that are results of the process of internal displacement, patriarchal family structure has come out as an important factor that prevented particularly young Kurdish women from participating in such activities. On the other hand, relatively older Kurdish women could not participate in vocational and literacy courses because they lacked language skills in Turkish, leading them to demand education in the mother tongue. Most of the Kurdish women could not join educational facilities due to the density of household jobs and care for children as a result of social gender roles. Finally, being internally displaced has created a negative attitude among Kurdish women towards the state. The findings were discussed by constant comparison and contrast with global views on gender dimensions of internal displacement.
Keywords: Internally displaced persons -- Kurdish women.; Social work with immigrants.; Women -- Education -- Turkey.